Review of Energy Management Strategies in Engineering Projects: Optimization of Resources and Efficiency - Naeini, Amir (Management Strategies and Engineering Sciences, 2023)
The increasing demand for energy efficiency and sustainability in engineering projects has brought energy management and resource optimization to the forefront of industry practices. This narrative review explores the evolution of energy management strategies, focusing on the optimization of resources and efficiency within engineering projects. It examines key theoretical frameworks and highlights the role of advanced technologies, such as simulation models, artificial intelligence (AI), and the Internet of Things (IoT), in enhancing resource optimization. Through an analysis of case studies, the review demonstrates the significant impact of resource optimization on energy efficiency, cost savings, and sustainability. Moreover, it discusses the economic implications, including cost-benefit analyses and return on investment, and the critical role of resource optimization in achieving sustainability goals. The review identifies gaps in the current literature, particularly regarding the high costs of implementation and the need for standardized metrics, and suggests future research directions to advance the practice of energy management in engineering projects.